Penerapan Undang-Undang Nomor 30 Tahun 2009 Tentang Ketenagalistrikan di Pulau Batam - Jon Ledi Silas (Fakultas Hukum, Universitas Internasional Batam, 2014)
This study examined the implementation of Law No. 30 of 2009 (the Electricity Law) in Batam Island by focusing research on PT PLN Batam as the main and largest electricity supplier in Batam Island. The results of the study found out that the implementation of the Electricity Law in Batam Island by the Batam City Government was not fair, especially on issuing the electricity business permit, business area and tariffs Batam Island. The Batam City Government as the holder of authority to carry out the regulatory functions should implement policies that favor the balance of interests of national, regional, consumers, and the electricity providers for the sake of the macro interests and the future of electricity in Batam Island.Special attentions from the Batam City Government and other stakeholders are needed in order to make sure that PT PLN Batam can be managed professionally, able to support itself, and able to develop continuously because of the performance and development of PT PLN Batam directly impacted the general development of electricity and that ultimately also determined the development of the economy and the welfare of society in the islands of Batam, Rempang and Galang.